Bioinformatics analysis identifies immune-related gene signatures and subtypes in diabetic nephropathy - Lu, Kunna; Wang, Li; Fu, Yan; Li, Guanghong; Zhang, Xinhuan; Cao, Mingfeng (Frontiers in Endocrinology, 2022)
Background: Systemic inflammation and immune response are involved in the pathogenesis of diabetic nephropathy (DN). However, the specific immune-associated signature during the DN development is unclear. Our study aimed to reveal the roles of immune-related genes during DN progression. Methods: The GSE30529 and GSE30528 datasets were acquired from the Gene Expression Omnibus (GEO) database. Then, the intersection between differentially expressed genes (DEGs) and immune score-related genes (ISRGs) was screened. Subsequently, functional enrichment analyses were performed. The different immune phenotype-related subgroups were finally divided using unsupervised clustering. The core genes were identified by WGCNA and protein-protein interaction (PPI) network. xCell algorithm was applied to assess the proportion of immune cell infiltration. Results: 92 immune score-related DEGs (ISRDEGs) were identified, and these genes were enriched in inflammation- and immune-associated pathways. Furthermore, two distinct immune-associated subgroups (C1 and C2) were identified, and C1 subgroup exhibited activated immune pathways and higher percentage of immune cells compared to C2 subgroup. Two core genes (LCK and HCK) were identified and all up-regulated in DN, and the expressions were verified using GSE30122, GSE142025, and GSE104954 datasets. GSEA indicated the core genes were mainly enriched in immune-related pathways. Correlation analysis indicated LCK and HCK expressions were positively correlated with aDC, CD4+ Tem, CD8+T cells, CD8+ Tem, and mast cells. Conclusions: We identified two immune-related genes and two immune associated subgroups, which might help to design more precise tailored immunotherapy for ND patients.